2005
DOI: 10.1088/1126-6708/2005/02/052
|View full text |Cite
|
Sign up to set email alerts
|

Non-minimally Coupled Tachyonic Inflation in Warped String Background

Abstract: Abstract:We show that the non-minimal coupling of tachyon field to the scalar curvature, as proposed by Piao et al, with the chosen coupling parameter does not produce the effective potential where the tachyon field can roll down from T = 0 to large T along the slope of the potential. We find a correct choice of the parameters which ensures this requirement and support slow-roll inflation. However, we find that the cosmological parameter found from the analysis of the theory are not in the range obtained from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…One reason is that the tachyon field perturbations around the unstable vacuum must contain an unstable mode whose (negative) eigenvalue is the tachyon mass squared, which is of order the string scale. This leads to an η-problem in tachyonic inflation [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…One reason is that the tachyon field perturbations around the unstable vacuum must contain an unstable mode whose (negative) eigenvalue is the tachyon mass squared, which is of order the string scale. This leads to an η-problem in tachyonic inflation [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]. The cosmological implications of the tachyon were studied in [74][75][76][77][78][79][80][81][82][83][84][85][86]. For more details see also Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Inflationary paradigm [75][76][77][78][79][80][81][82][83][84][85][86]92], 2. Primordial non-Gaussianity and CMB aspects [96][97][98][99][100][101][102][103][104], 3.…”
Section: Introductionmentioning
confidence: 99%
“…One of the popular class of models is based on a scenario with a brane moving toward a localized antibrane, where the position of the mobile brane plays the role of the inflaton field [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In another approach, for inflation model building, the open string tachyon field described by a nonstandard action [20], which lives in a world volume of a non-BPS brane, has been used as the inflaton field [21][22][23][24][25][26][27][28]. It was observed that the same non-standard tachyon effective action also describes the dynamics of a mobile BPS brane in the background of a stack of BPS branes [29][30][31].…”
Section: Introductionmentioning
confidence: 99%